EFFECT OF PROBIOTIC SUPPLEMENTATION ON PERFORMANCE OF CROSSBRED KIDS UNDER STALLFED CONDITIONS ALLFED CONDITIONS - A. K. SRIVASTAVA; CHARAN SINGH; H. D.CHAUHAN; SANJAY KUMAR (The Bioscan, 2018)
Thirty crossbred (Alpine x Beetal) female kids (50-60 days age) were randomly divided into three groups based on body weight. Feeding schedule comprised of concentrate and green fodder berseem ad-lib. (Control-C1). Kids of probiotic supplemented groups in addition to control ration, received commercial probiotic supplement of “Biobloom”(Sarabhai-Zydus) @ 2 gm/day/kid (Treatment-T1 ) and 3 gm/day/kid (Treatment-T2 ), mixed in concentrate ration. Overall body weight gain during the 15 weeks experimental period (kg) was significantly (P<0.01) higher in T1 (10.02±0.32) and T2 (10.52±0.50) than control (8.05±0.44). ADG (g/day) was also significantly (P<0.01) higher in T1 (95.43±2.77) and T2 (100.19±4.31) than control (76.67±3.79). Kids of T1 and T2 consumed 3.37% and 4.26% more feed than control, respectively. The FCR was significantly (P<0.01) better in T1 (6.54±0.25) and T2 (6.42±0.32) than control (8.44±0.96). Number of kids affected with health problems was significantly (P<0.01) higher in control (9) than T1 (5) and T2 (3) groups. Similarly total duration of disease affection (days) was significantly (P<0.01) higher in control (35) than T1 (13) and T2 (6) groups. Optimum dose of probiotic supplementation was found 2gm/kid/day in the present study. It was concluded that the probiotic supplementation enhanced the performance of crossbred female kids under stallfed conditions.